2006
DOI: 10.1016/j.cardiores.2005.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of COX-2 in VEGF-induced angiogenesis via P38 and JNK pathways in vascular endothelial cells

Abstract: COX-2 plays an important role in VEGF-induced angiogenesis via p38 and JNK kinase activation pathways. These findings suggest that the cardioprotective role of COX-2 may be, at least in part, through its angiogenic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
125
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 19 publications
15
125
1
3
Order By: Relevance
“…Functionally, JNK is an important part of learning and memory systems (Sherrin et al, 2011). And there is at least one study suggesting that JNK may mediate angiogenesis in human umbilical vein endothelial cells (Wu et al, 2006). Our present findings might be consistent with this broader literature.…”
Section: Discussionsupporting
confidence: 93%
“…Functionally, JNK is an important part of learning and memory systems (Sherrin et al, 2011). And there is at least one study suggesting that JNK may mediate angiogenesis in human umbilical vein endothelial cells (Wu et al, 2006). Our present findings might be consistent with this broader literature.…”
Section: Discussionsupporting
confidence: 93%
“…Sorafenib inhibits multiple receptors, including members of the VEGFR family. VEGF activates JNK in human umbilical vascular endothelial cells (46) in a pathway that likely involves cdc42 and VEGFR-2 (47,48). Given the pleiotropic nature of sorafenib and proteasome inhibitors, it is likely that multiple pathways are contributing to the synergistic activation of JNK that we report in response to combined treatment.…”
Section: Discussionmentioning
confidence: 75%
“…For example, blocking the VEGF pathway abolishes the proangiogenic and protumorigenic effects of EETs (11,(35)(36)(37). COX-2 inhibition has been shown to inhibit VEGF production (38); thus, coinhibition of COX-2 may reduce or eliminate the proangiogenic effects of EETs. As expected here, we also found that PTUPB reduced the plasma VEGF level by 50%.…”
Section: Cox-2/seh Dual Inhibitor Ptupb Inhibits Primary Tumor Growthmentioning
confidence: 99%